Kajian Perbandingan Pelaksanaan Program Perkembangan Profesionalisme Guru di Sebuah Menengah Indonesia di Malaysia dan Indonesia - Anwar Zarkasi (Menara Tebuireng, 2018)
The purpose of this study was to describe the implementation of the teacher professionalism development program in Indonesia Secondary School in Malaysia and in Indonesia. A quantitative study method was used in this study. This study is specially for recognize the form of teacher professionalism development program that hold in The Indonesia Secondary School in Malaysia and in Indonesia, besides effectiveness of this program and its influences to teacher’s work satisfaction. Research was conducted in Indonesia Secondary School in Malaysia and Indonesia, research population consist of 79 of teachers in the both schools. Sample taken purposively, namely who has experiences of teaching more than three years in the schools. The data of this study was collected from inquiries that consists of 42 items that are tested by Alpha Crombach approach for reliability. Additional data was collected through document analysis and the in-depth interviews. The collected data are analyzed using SPSS version 12. The finding of the study showed that teacher professionalism development program was done through teacher conference, teaching observation, and other activities. The method that very often use in the program are the speech, dialog, teaching demonstration, and watching video, that suitable for the teachers like in Indonesia, but not for teachers in Malaysia who see watching video method as the most suitable method for them. Totally, the program of teacher professionalism development, both in Malaysia and in Indonesia gave some benefits for up gadding of teacher’s quality in the schools. However, the aspects of objectives achievements and attained benefits showed that implementation of the program of teacher professionalism development in Malaysia was not effective, on the other hand in Indonesia it did effectively. In spite of this, no significant differences about the implementation of the program of teacher professionalism development in Malaysia and in Indonesia. Further more the study also proofed the positive correlation between teacher professionalism program and teacher work satisfaction